Contrasting responses of black fly species (Diptera: Simuliidae) to experimental whole‐stream warming. (9th July 2020) - Nelson, Daniel; Benstead, Jonathan P.; Huryn, Alexander D.; Cross, Wyatt F.; Hood, James M.; Johnson, Philip W.; Junker, James R.; Gíslason, Gísli M.; Ólafsson, Jón S.
Abstract: As global temperatures continue to rise, assessment of how species within ecological communities respond to shifts in temperature has become increasingly important. However, such assessments require detailed long‐term observations or ecosystem‐level manipulations that allow for interactions among species and the potential for species dispersal and exchange with the regional species pool. We examined the effects of experimental whole‐stream warming on a larval black fly assemblage in southwest Iceland. We used a paired‐catchment design, in which we studied the warmed stream and a nearby reference stream for 1 year prior to warming and 2 years during warming and estimated population abundance, biomass, secondary production, and growth rates for larvae of three black fly species. Experimental warming by 3.8°C had contrasting effects on the three black fly species in the assemblage. The abundance, biomass, growth, and production of Prosimulium ursinum decreased in the experimental stream during the warming manipulation. Despite increasing in the reference stream, the abundance, biomass, and production of another species, Simulium vernum, decreased in the experimental stream during warming. In contrast, warming had an overall positive effect on Simulium vittatum . While warming had little effect on the growth of overwintering cohorts of S. vittatum, warming led to an additional cohort during the summer months and increased its abundance, biomass, and production. Overall, family‐level production was enhanced by warming, despite variation in species‐level responses. Our study illustrates that the effects of climate warming are likely to differ even among closely related species. Moreover, our study highlights the need for further investigation into the uneven effects of warming on individual species and how those variable effects influence food web dynamics and ecosystem function.